Inibição sistêmica da NADPH oxidase: estudo do coração de ratos espontaneamente hipertensos com diabetes mellitus - Bassetto, Camila Moreno Rosa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Cardiovascular diseases (CVD) are the major cause of morbidity and mortality worldwide. Diabetes mellitus (DM) and arterial hypertension (AH) are the main risk factors for the development of CVD. The coexistence of diabetes and hypertension is common and leads to an increased risk of cardiovascular events. Organs damage caused by hypertension and DM have been associated with increased oxidative stress. Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase enzymes family is a major source of reactive oxygen species in the cardiovascular system. Apocynin (APO) has been characterized as an inhibitor of NADPH oxidase since the 1980's decade. Despite promising evidence of APO in the treatment of many diseases, there are studies questioning its power as an inhibitor of NADPH oxidase. Besides controversies on the use of apocynin in blocking NADPH oxidase in non-phagocytic cells, few studies have evaluated the effects of its blockade on cardiac remodeling. In addition, there is a lack of information when AH and DM are associated. Therefore, the aim was to analyze the influence of NADPH oxidase inhibition by apocynin on cardiac remodeling in spontaneously hypertensive rats (SHR) with diabetes mellitus. Methods: Seven-month-old male SHR were divided into four groups: control (CTL, n=18); CTL+APO (n=18); DM (n=20); DM+APO (n=20). DM was induced by streptozotocin (40 mg/kg, i.p., single dose). CTL+APO and DM+APO groups received APO (16 mg/kg/day, diluted in the water) for 8 weeks. In vivo cardiac structures and functions were assessed by echocardiogram. In vitro functional study was performed by left ventricular papillary muscle study. In vitro left ventricle (LV), right ventricle and atria weights were measured. Samples of these structures, liver and lung were used to calculate the wet/dry weight ratio. LV tissue samples were obtained to measure myocyte diameters, interstitial collagen fraction, and hydroxyproline concentration. Left ...

As doenças cardiovasculares (DCV) são a maior causa de invalidez e mortalidade em todo o mundo. Entre os principais fatores de risco para o desenvolvimento das DCV estão o diabetes mellitus (DM) e a hipertensão arterial sistêmica (HAS). Frequentemente, há co-existência de DM e HAS e isso ocasiona aumento do risco de eventos cardiovasculares. Os danos causados tanto pela HAS como pelo DM têm sido associados com o aumento do estresse oxidativo. A família de enzimas nicotinamida adenina dinucleotídeo fosfato (NADPH) oxidase constitui uma das principais fontes de produção de espécies reativas de oxigênio no sistema cardiovascular. A apocinina (APO) tem sido caracterizada como um inibidor da NADPH oxidase desde a década de 1980. Apesar de evidências promissoras do uso da APO no tratamento de inúmeras doenças, há estudos questionando seu poder inibidor da NADPH oxidase. Além de controvérsias do uso da APO no bloqueio da NADPH oxidase em células não fagocíticas, poucos estudos avaliaram os efeitos desse bloqueio sobre o remodelamento cardíaco. Além disso, a escassez de informações é maior quando se associa HAS e DM. Portanto, o objetivo foi analisar a influência da inibição da NADPH oxidase por apocinina sobre o remodelamento cardíaco em ratos espontaneamente hipertensos (SHR) com diabetes mellitus. Métodos: SHR, machos, com 7 meses de idade, foram divididos em quatro grupos: controle (CTL, n=18), controle+apocinina (CTL+APO, n=18); diabético (DM, n=20) e diabético+apocinina (DM+APO, n=20). DM foi induzido por estreptozotocina (40 mg/kg, ip, dose única). Os grupos CTL+APO e DM+APO receberam APO (16 mg/kg/dia, diluída na água dos animais) durante 8 semanas. A avaliação estrutural e funcional in vivo do coração foi realizada por meio do ecocardiograma. O estudo funcional in vitro foi realizado pela técnica do músculo papilar do ventrículo esquerdo (VE). Para análise estrutural in vitro, foram medidos os...
Keywords: Diabetes mellitus; Hipertensão; Stress oxidativo; NADPH Oxidase; Hypertension